CEO Connectedness and Corporate Fraud - KHANNA, VIKRAMADITYA; KIM, E. HAN; LU, YAO (Journal of Finance, 2015)
ABSTRACT We find that connections CEOs develop with top executives and directors through their appointment decisions increase the risk of corporate fraud. Appointment‐based CEO connectedness in executive suites and boardrooms increases the likelihood of committing fraud and decreases the likelihood of detection. Additionally, it decreases the expected costs of fraud by helping conceal fraudulent activity, making CEO dismissal less likely upon discovery, and lowering the coordination costs of carrying out illegal activity. Connections based on network ties through past employment, education, or social organization memberships have insignificant effects on fraud. Appointment‐based CEO connectedness warrants attention from regulators, investors, and corporate governance specialists.